A Congestion-Aware IDS Node Selection Method for Wireless Sensor Networks. (31st July 2012) - Choi, Jaeun; Kim, Gisung; Kim, Sehun
Abstract : We propose an Intrusion Detection System (IDS) node selection method for Wireless Sensor Networks (WSNs). Due to the WSNs' distinctive tree structure, network congestion normally occurs in nodes that are located in the vicinity of a static base station. Moreover, in resource-constrained WSNs, network congestion could occur due to resource depletion attacks, such as Denial of Service (DoS) attacks. This congestion increases data loss and reduces the network's lifetime. In this paper, we propose an Intrusion Detection Systems (IDSs) construction method that considers this network congestion. Moreover, due to the limited battery life of sensor nodes, the proposed method is considered to be efficient in utilizing limited resources by selecting IDS nodes that enhance the network's lifetime and reduce the total energy consumption. The simulation results show that the proposed method enhances the network's lifetime and reduces the total energy consumption of the congested network.